Impact of Hydrogen‐Rich Silicon Nitride Material Properties on Light‐Induced Lifetime Degradation in Multicrystalline Silicon. Issue 8 (26th April 2019) - Bredemeier, Dennis; Walter, Dominic C.; Heller, René; Schmidt, Jan
Abstract : The root cause of "Light and Elevated Temperature Induced Degradation" (LeTID) of the carrier lifetime in multicrystalline silicon (mc‐Si) wafers is investigated by depositing hydrogen‐rich silicon nitride (SiN x :H) films of different compositions on boron‐doped mc‐Si wafers. The extent of LeTID observed in mc‐Si after rapid thermal annealing (RTA) shows a positive correlation with the amount of hydrogen introduced from the SiN x :H layers into the bulk. The concentration of in‐diffused hydrogen is quantified via measuring the resistivity change due to the formation of boron–hydrogen pairs in boron‐doped float‐zone silicon wafers processed in parallel to the mc‐Si wafers. The measurements clearly show that the in‐diffusion of hydrogen into the silicon bulk during RTA depends on both the atomic density of the SiN x :H film as well as the film thickness. Importantly, the impact of SiN x :H film properties on LeTID shows the same qualitative dependence as the hydrogen content in the silicon bulk, providing evidence that hydrogen is involved in the LeTID defect activation process. Abstract : Multicrystalline silicon lifetime samples coated with hydrogen‐rich silicon nitride films are prone to show a pronounced lifetime degradation under illumination at elevated temperature. This study shows that hydrogen is involved in the defect which is frequently abbreviated as LeTID. The concentration of in‐diffused hydrogen is quantified via measuring resistivity changes due to the formation of boron–hydrogen pairs in parallel processed boron‐doped float‐zone silicon wafers.